Formação docente das competências digitais tecnológicas: práxis docente construtivista para a educação profissional - Melo, Domingos Sávio Ferreira de (2023)
Based on new educational methodologies centered on innovative technologies, teachers attempt to integrate technological artifacts into their teaching practices through their planning. This requires proposing actions capable of identifying their digital competences (DCs). Therefore, this research aimed to find out how teachers in Professional and Technological Education ("PTE") measure and develop the levels of their DCs. In this sense, the main objective of this research was to develop a training proposal for teachers working in PTE through the implementation of DigCompEdu in the Moodle Virtual Learning Environment (VLE), with the purpose of helping them to improve and measure their digital competencies in order to contribute to the teaching and learning process of students through innovative technological teaching resources. Thus, the locus of the research were two Professional and Technological Education Schools (PTE) in the city of Quixadá-CE. In view of the above, this research is an exploratory study with a qualitative approach, in which data was collected and analyzed using three questionnaires. The data was processed and analyzed using Bardin's (2016) content analysis. The research subjects were 22 teachers who completed all the stages of the research, corresponding to a sample of 42% of the universe of teachers from the schools surveyed. The results of the study showed that they still find it difficult to measure and develop their DCs, and that they still apply mechanisms found and selected on their own to solve the main problems in the classroom. In addition, the training that is currently available is not yet reflected in teachers' practice, and teachers only know that the tools exist and that they can be used, but they don't have an experience and a mechanism that is directed at the curricular components.